Effect of some Selected Nursery Practices on Growth and Development of Marinoo (Ulmus laevigata) Seedlings - Bhardwaj, S. D.; Shamet, G. S.; Lal, Purshotam (Indian Forester, 1995)
The paper describes the effect of four spacings with four levels and two split application of nitrogen on growth and biomass production of Ulmus laevigata seedlings. Applications of 80 kg N/ha in two equal splits (½ at transplanting + ½ after 30 days of transplanting) with 20 × 15 cm spacing proved most promising for producing more biomass per plant and healthy and vigorous nursery stock.